A case of coronary artery aneurysm after sirolimus-eluting stent implantation presenting with unstable angina due to progression of stent thrombosis: Concerns over sirolimus-eluting stents remain. Issue 6 (December 2016) - Matsui, Shogo; Ikeda, Shuntaro; Aono, Jun; Higashi, Haruhiko; Ohshima, Kiyotaka; Hamada, Mareomi
Abstract: A 44-year-old man was implanted with a sirolimus-eluting stent in the proximal left anterior descending artery 8 years previously. Six years later, multi-slice computed tomography and angiography confirmed the formation of a coronary artery aneurysm around the stent. Optical coherence tomography revealed organized thrombi within the stent. Eight years after implantation, the patient presented with chest pain, and multiple imaging modalities revealed thrombotic occlusion within the stent. Surprisingly, the coronary artery aneurysm became a detour for distal flow from the occluded stent. Long-term follow-up after implantation of first-generation drug-eluting stents is mandatory, because unexpected reactions can suddenly occur. <Learning objective: The present case experienced two episodes of unstable angina in very late stage after sirolimus-eluting stent implantation. In addition to the chronic inflammatory reactions and progressive positive remodeling, turbulent and sluggish blood flow within the aneurysm may have resulted in the stagnation of coronary flow, leading to multiple episodes of very late stent thrombosis. Careful and long-term follow-up using multiple imaging modalities should be mandatory after the first drug-eluting stent implantation.>